INNOVATION IN ECONOMICS AND FINANCE - Zh. O. Lukpanova; Zh. A. Toyzhigitova; A. A. Kazhmukhametova (Academic Journal of Physical and Chemical Sciences, 2019)
It is shown that, despite a significant increase in innovation activity in the financial sector of the economy, a large number of developments in this area, some gaps remain related to the practical application, introduction of financial innovations, the use of innovative tools in the field of financial technologies in the Russian economy, the definition of the role and places of financial innovation in the overall structure of the financial sector of the economy. Studied the main trends in the development of the digital economy. It is convenient for people to exchange money in the process of communication without using any separate applications. Therefore, other companies have followed the example: options for sending money in the chat now offer, in addition to the aforementioned Apple, Facebook, Google, Vk.